Information transmission efficiency between housing and land markets: an empirical study in China - Lan, Zhengqiu (2016)
In recent years, Chinese central government has introduced several rounds of macro-control policies to stabilize the development of real estate market. However, the regulatory effect is not significant. Actually, the regulating effect of macro-policies depends on the market efficiency largely, especially the information transmission efficiency inner and between housing market and land market. Firstly, this thesis studies the information transmission efficiency of Chinese real estate market. The results show that no matter for the mean information and volatility information, there is only unidirectional transmission from land market to housing market , so land market is the information center. The information of land market will be reflected in housing prices in the next period. Meanwhile, the housing market is much more informationally efficient, as it responds to new information faster. Secondly, this thesis studies the effect of IAL system and HPR on the information transmission efficiency between Chinese housing market and land market. The results show that, for the mean and volatility information, both IAL system and HPR decrease the transmission efficiency. Firstly, the mean information transmission channel changes from one to zero after the implementation of IAL system. Secondly, after the implementation of the two policies, the bidirectional volatility transmission between the two markets changes to unidirectional transmission or no transmission. Thirdly, the inner information transmission efficiency of housing and land markets both decrease after the implementation of the two policies.